The Aegis orbit determination and impact monitoring system and services of the ESA NEOCC web portal - Fenucci, Marco; Faggioli, Laura; Gianotto, F.; Bracali Cioci, D.; Cano, Jorge L.; Conversi, L.; Devogèle, M.; Di Girolamo, G.; Drury, C.; Föhring, D.; Gisolfi, L.; Kresken, R.; et al. (Springer, 2024)
The NEO Coordination Centre (NEOCC) of the European Space Agency is an operational centre that, among other activities, computes the orbits of near-Earth objects and their probabilities of impact with the Earth. The NEOCC started providing information about near-Earth objects in 2012 on a dedicated web portal, accessible at https://neo.ssa.esa.int/. Since the beginning of the operational phase, many developments and improvements have been implemented regarding the software, the data provided, and the portal. One of the most important upgrades is that the NEOCC is now independently providing data through a newly developed Orbit Determination and Impact Monitoring system, named Aegis. All the data computed by Aegis are publicly available on the NEOCC web portal, and Aegis is also used to maintain all the major services offered. The most important services comprise an orbital catalogue of all known asteroids, a list of possible future impacts with the Earth (also called Risk List), a list of forthcoming close approaches, a set of graphical toolkits, and an on-demand ephemerides service. Many of the services are also available through dedicated APIs, which can be used to automatically retrieve data. Here we give an overview of the algorithms implemented in the Aegis software and provide a summary of the services offered by the NEOCC that are supported by Aegis.
Keywords: 5109 Space Sciences; 51 Physical Sciences; Astronomy & Astrophysics; 5101 Astronomical sciences